Distribution of charophyte species in Estonian coastal water (NE Baltic Sea) - Torn, Kaire; Martin, Georg; Kukk, Henn; Trei, Tiiu (Scientia Marina, 2004)
Charophytes constitute a group of macrophytes that usually inhabit soft bottoms with shallow water. They occur mostly in fresh-water environments but can also be found in brackish waters. Due to their requirement for clear water they are considered sensitive to eutrophication and therefore often used as an indicator for good water quality. The diverse structure of the Estonian coastline with its numerous sheltered bays and shallow, soft-bottom archipelago areas coupled with low salinity conditions provides an excellent habitat for charophytes. To date, seven species have been described in Estonian coastal waters, NE Baltic Sea. Last systematic investigations on charophyte distribution date back 20-30 years. During the summer of 2001 the locations where charophytes have previously been found were revisited and new sites sampled, to describe the present distribution of quantitative and qualitative parameters of charophyte species. Sampling was performed mainly by SCUBA diving; occurrence, abundance and wet weight biomass were estimated for each location. Six species of charophytes were identified. Compared to previously recorded material, no significant changes in the distribution pattern of charophytes were found. The dependence of charophyte distribution on environmental settings was tested, with depth and substrate quality explaining most of the variability in distribution. Salinity within observed range had minor influence on charophytes.